Phân loại trượt lở đất đá và đánh giá nguy cơ trượt lở dọc tuyến đường Hồ Chí Minh thuộc Hà Tĩnh - Hải, Nguyễn Tiến; An, Bùi Phong (Vietnam Journal of Earth Sciences, 2012)
SUMMARYCurrent status and risk estimation of landslide hazard along the Hochiminh roads in Hatinh ProvinceLandslide is a natural hazard often occurs in hilly and mountainous regions of Vietnam; especially along newly widened and newly constructed roads. Consequences of landslide hazard are to pill upmany section roads and frequently causing serious damages to residential areas as well as constructions situated along the roads.Based on field investigations in two years (2009 - 2010), intergrated wih tophographical and images analysis, and other geological data as well, this paper analyzes the current status and to classify of landslidealong Hochiminh roads in Hatinh province, and to estimate their danger. The paper also analyzes geological, geomorphological, meteorological - hydrographical, and human causes which impacted to landslide in the study area and set of preventing solusions to this natural hazard have been proposed.